2013
DOI: 10.1371/journal.pone.0055148
|View full text |Cite
|
Sign up to set email alerts
|

Spatial Variations in Microbial Community Composition in Surface Seawater from the Ultra-Oligotrophic Center to Rim of the South Pacific Gyre

Abstract: Surface seawater in the South Pacific Gyre (SPG) is one of the cleanest oceanic environments on earth, and the photosynthetic primary production is extremely low. Despite the ecological significance of the largest aquatic desert on our planet, microbial community composition in the ultra-oligotrophic seawater remain largely unknown. In this study, we collected surface seawater along a southern transect of the SPG during the Integrated Ocean Drilling Program (IODP) Expedition 329. Samples from four distinct sit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

8
63
2

Year Published

2014
2014
2020
2020

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 74 publications
(73 citation statements)
references
References 52 publications
(59 reference statements)
8
63
2
Order By: Relevance
“…During the entire year, the euphotic zone and the mixed layer were dominated by Bacteria, while Archaea were only a minor constituent, as was found elsewhere (41,42). SAR11 was the most abundant phylogenetic group and regularly accounted for more than 40% of the communities.…”
Section: Discussionmentioning
confidence: 54%
“…During the entire year, the euphotic zone and the mixed layer were dominated by Bacteria, while Archaea were only a minor constituent, as was found elsewhere (41,42). SAR11 was the most abundant phylogenetic group and regularly accounted for more than 40% of the communities.…”
Section: Discussionmentioning
confidence: 54%
“…Instead, rhodopsin abundance has been calculated based on metagenomic sequence data (3,12,24,25), amplicon sequencing (15,26,27), quantitative PCR (QPCR) (27,28), or cultivation (15,(29)(30)(31). These estimates show that in some marine environments, up to 70% of the cells may host a rhodopsin (3), while up to 30% are Chl a-containing cyanobacteria (32,33) and an additional 1 to 30% contain BChl a (34). In nonmarine aquatic environments, 35 to 62% of genomes within metagenomic assemblies harbor a rhodopsin (14), while analysis of freshwater bacterioplankton metagenomic assemblies and single amplified genomes from the same locations suggested the presence of a rhodopsin in 37 to 56% and 8 to 20% of the samples, respectively (35).…”
mentioning
confidence: 99%
“…Similar most abundant taxa were also among the most abundant on the surfaces of crustose coralline algae, CCA (Sneed et al, 2015). Cyanobacteria, which were found in highest numbers at the inshore site (LL), are often an indicator for bad water quality and eutrophic conditions (Agawina et al, 2003;Paerl et al, 2011) and may inhibit coral recruitment (Charpy et al, 2012), while Alphaproteobacteria, which had the lowest abundance at the inshore site, are often associated with more oligotrophic systems (Yin et al, 2013) and were found to be dominant on CCA surfaces, where their decrease was shown to reduce coral larvae settlement (Webster et al, 2011). These findings corroborate the assumption that the environmental conditions at the inshore site, which was most affected by anthropogenic impacts from nearby Makassar, accommodate a certain BCC accustomed to these conditions.…”
Section: Bacterial Communitiesmentioning
confidence: 98%